Management Challenges in Atypical Femoral Fractures: A Case Report - Mohammad Golsorkhtabaramiri; Charles A. Inderjeeth (Annals of Geriatric Medicine and Research, 2020)
A 78-year-old woman presented with an atypical femoral fracture of her right femur associated with a left thigh stress fracture following 9 years of bisphosphonate therapy. The fracture was managed with femoral nailing. However, she represented 3 years later with peri-prosthetic infection, worsening of the left-side stress fracture, and low bone turnover in a bone metabolic study, consistent with an ongoing bisphosphonate effect. This case highlights the increased rate of postoperative complications in atypical femoral fractures even years after surgery as well as the challenging management issues for contralateral fracture and the risk of missing bilateral fractures.